PENGARUH PENEMPATAN KERJA DAN KOMITMEN ORGANISASITERHADAP KINERJA KARYAWAN PADA PT. JASA RAHARJA CABANG SULAWESI TENGGARA - Abdul Muin Hamzah; Laode Asfahyadin Aliddin; Abd. Razak Yusuf; Nurwati Nurwati; Sri Wiyati Mahrani (Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims: (1) To determine the effect of work placement and organizational commitment on employee performance at PT. Jasa Raharja Southeast Sulawesi Branch; (2) To determine the effect of Work Placement on employee performance; (3) To determine the effect of organizational commitment on employee performance. The population used in this study were all employees of PT. Jasa Raharja Southeast Sulawesi Branch, totaling 30 people who were also used as the respondent unit. The analysis used is quantitative analysis using Multiple Linear Regression Analysis. The results showed that; (1) Work placement and organizational commitment simultaneously have a significant positive effect on the performance of employees of PT. Jasa Raharja Southeast Sulawesi Branch; (2) Job placement has a significant positive effect on employee performance; (3) Organizational commitment has a significant positive effect on employee performance.